KEBIJAKAN SEKURITISASI DAN PERSEPSI ANCAMAN DI LAUT NATUNA UTARA [THE POLICY OF SECURITIZATION AND THREAT PERCEPTION IN NORTH NATUNA SEA] - Ramdhan Muhaimin (Jurnal Politica, 2018)
AbstractThe Government of the Republic of Indonesia released a new national map in July 2017. One of the new is the renaming of the northern waters of Natuna Island (Riau Islands Province) as the North Natuna Sea, which was previously included in the naming of the South China Sea. The policy of renaming has gained hard protest from China, one of Asia's biggest nations which has experienced significant economic and defense growth in the last two decades. The renaming policy of the sea is an interesting study because the policy was released when the escalation of security dynamics in the South China Sea is warming up. This study uses the concept of threat perception, and theory of securitization developed by Copenhagen School. The purpose of the conceptual approach in this security study, to prove that the renaming policy of the North Natuna Sea can be seen as an attempt to securitize Indonesia's national interests from external threats.AbstrakPemerintah Republik Indonesia merilis peta baru pada Juli 2017 lalu. Salah satu yang berubah dalam peta baru RI adalah penamaan kawasan perairan di sebelah utara Pulau Natuna Provinsi Kepulauan Riau sebagai Laut Natuna Utara, yang sebelumnya masuk dalam penamaan Laut China Selatan. Kebijakan penamaan ulang laut ini mendapatkan protes keras dari China, salah satu negara besar Asia yang dalam dua dekade terakhir mengalami pertumbuhan ekonomi dan pertahanan signifikan. Kebijakan perubahan nama laut ini menjadi kajian menarik karena kebijakan tersebut dilakukan ketika eskalasi dinamika keamanan di Laut China Selatan sedang menghangat. Kajian ini menggunakan konsep persepsi ancaman dan teori sekuritisasi yang dikembangkan Mazhab Copenhagen (Copenhagen School). Tujuan pendekatan konseptual dalam studi keamanan ini, untuk melihat apakah kebijakan penamaan ulang Laut Natuna Utara dapat dilihat sebagai upaya sekuritisasi kedaulatan kepentingan nasional Indonesia dari ancaman eksternal.